Живые и мертвые: роман в 3 книгах - Симонов Константин Михайлович (1981)
Экземпляры: ЧЗ (20160616) / Инвентарный номер: 535 / Цена: 2.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: С 37 / ГРНТИ: 17 / ББК: 84(2Рос=Рус)6